The influence of nutritional state on the fatty acid composition of circulating lipid fractions: implications for their use as biomarkers of dietary fat intake - Parry, S; Rosqvist, F; Peters, S; Young, R; Cornfield, T; Dyson, P; Hodson, L (Taylor and Francis, 2021)
Background: The fatty acid (FA) composition of blood can be used as an objective biomarker of dietary FA intake. It remains unclear how the nutritional state influences the FA composition of plasma lipid fractions, and thus their usefulness as biomarkers in a non-fasted state. Objectives: To investigate the associations between palmitate, oleate and linoleate in plasma lipid fractions and self-reported dietary FA intake, and assess the influence of meal consumption on the relative abundance of these FA in plasma lipid fractions (i.e. triglyceride [TG], phospholipids [PLs] and cholesterol esters [CEs]). Design: Analysis was performed in plasma samples collected from 49 (34 males and 15 females) participants aged 26–57 years with a body mass index (BMI) between 21.6 and 34.2 kg/m2, all of whom had participated in multiple study visits, thus a pooled cohort of 98 data sets was available for analysis. A subset (n = 25) had undergone nutritional interventions and was therefore used to investigate the relationship between the FA composition of plasma lipid fractions and dietary fat intake. Results: Significant (P < 0.05) positive associations were observed between dietary polyunsaturated fat and linoleate abundance in plasma CE. When investigating the influence of meal consumption on postprandial FA composition, we found plasma TG palmitate significantly (P < 0.05) decreased across the postprandial period, whereas oleate and linoleate increased. A similar pattern was observed in plasma PL, whereas linoleate abundance decreased in the plasma CE. Conclusion: Our data demonstrate that the FA composition of plasma CE may be the lipid fraction to utilise as an objective biomarker when investigating recent (i.e. previous weeks-months) dietary FA intakes. In addition, we show that the consumption of a high-fat meal influences the FA composition of plasma TG, PL and CE over the course of the postprandial period, and therefore, suggest that fasting blood samples should be utilised when using FA composition as a biomarker of dietary FA intake.